Efektifitas Pembelajaran Learning Cycle 5E Terhadap Prestasi Belajar Matematika - Nikmah Nor Hidayah; Irfan Wahyu Prananto (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
The purpose of this study is to analyze how effective the cycle learning model is towards student mathematics learning achievement by using puzzle mathematics media. This research is an experimental quantitative study carried out in class IV Gondosari Public Elementary School. The design of this research is the static group pretest-posttest desaign. The average mathematics achievement test results were 57.6 for the control class and 67.5 for the experimental class. The prerequisite test shows that the data are normally distributed and homogeneous. The research hypothesis test shows: (1) there is a difference in the average test of learning achievement (knowledge and skills) of mathematics between the experimental class and the control class that is 3,291 1,997; and (2) puzzle cycle assisted learning cycle cannot meet the classical effectiveness criteria.